2015
DOI: 10.1097/won.0000000000000179
|View full text |Cite
|
Sign up to set email alerts
|

Medical Adhesive-Related Skin Injury Prevalence Among Adult Acute Care Patients

Abstract: Medical adhesive-related skin injury is a prevalent event in the acute care setting. Preventing skin injury has the potential to reduce complications, increase patient satisfaction, and improve clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 8 publications
1
48
1
6
Order By: Relevance
“…MARSI is any type of problem in which erythema and/or other manifestation of cutaneous abnormality such as a vesicle, bulla, erosion or tear persists for 30 minutes or more after adhesive removal. MARSI is thought to develop in several forms; skin (epidermal) stripping, tension injury or blister, skin tear, irritant contact dermatitis, allergic dermatitis, maceration and folliculitis [2]. In our case there were abrasions on the eyelids which seemed close to skin tear defined by McNichol, et al However we also observed oozing hemorrhage on the lesions which made us think that the lesion could be categorized as abrasions [1].…”
Section: Discussionsupporting
confidence: 55%
“…MARSI is any type of problem in which erythema and/or other manifestation of cutaneous abnormality such as a vesicle, bulla, erosion or tear persists for 30 minutes or more after adhesive removal. MARSI is thought to develop in several forms; skin (epidermal) stripping, tension injury or blister, skin tear, irritant contact dermatitis, allergic dermatitis, maceration and folliculitis [2]. In our case there were abrasions on the eyelids which seemed close to skin tear defined by McNichol, et al However we also observed oozing hemorrhage on the lesions which made us think that the lesion could be categorized as abrasions [1].…”
Section: Discussionsupporting
confidence: 55%
“…Currently the burden of CASI on the healthcare environment is estimated by small single population studies,10,40 or as a secondary endpoint of interventional studies 30,41. Research is urgently needed to define the prevalence of CASI within the wider healthcare environment.…”
Section: Discussionmentioning
confidence: 99%
“…Four fictitious, but realistic case studies of patients with impaired skin at CVAD sites were developed by the authors using criteria evident in previous research that place patients at high risk for CASI 2,7,10. The case studies involved the description of CVAD sites with an exit site infection, skin injury, skin irritation/contact dermatitis, or noninfectious exudate; clinical information and photographs were provided for each fictitious case 2,4,7.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations